Isolation of environmental microorganisms from clinical specimens: A report of the occurrence of Acinetobacter anitratus in blood of hospitalized patients in Jakarta in a 7 year period (Faculty of Medicine Universitas Indonesia, 2009)
Aim To report the presence of environmental microorganisms, A. anitratus, in blood of hospitalized patients in Jakarta from 2002 to 2008 and their susceptibility to antibiotics. Methods A Retrospective study was performed on all blood specimens that were received in Clinical Microbiology Laboratory (CML) Faculty of Medicine University of Indonesia during 2002-2008. Culture and antimicrobial susceptibility examination were carried out according to up to date standard practice in CML and Clinical Laboratory Standard Institute, recpectively. Data was collected by WHONET 5.4 program. All Gram-negative microorganisms that were isolated from blood specimens were tabulated, and so the antibiotics susceptibility of A. anitratus. The origin of the specimens in term of institutions where the specimens came from was also analyzed. Results In a 7 year period up to 2008, A. anitratus was found in blood specimens, and these invironmental bacteria were in fact the most predominant isolated Gram negative microorganisms. Together with another environmental microorganism, Pseudomonas aeruginosa, it composed nearly 50%. Antimicrobial susceptibility test of this microorganism showed some degree of resistance to all tested antibiotics. The origin of those blood specimens which yielded A. anitratus were mainly from government-owned hospitals, that was 88 specimens (74%), followed by private hospitals (18 specimens, 15%), individuals (3 specimens, 3%), and unknown source (10 specimens, 8%). Conclusion Persistent occurrence of A. anitratus in blood specimens of hospitalized patients in hospitals in Jakarta was observed. In the near future, a study to fi nd risk factors for the acquisition of A. anitratus bacteremia is needed to reduce potential hospital associated infection. Moreover, genotyping is advised in order to determine the relationship of hospital and patient derived strains. (Med J Indones 2009; 18:227-32)